Effects of the behavioral activation in the life quality and emotional state for lung cancer patients - Fernández Rodríguez, Concepción; Villoria Fernández, Erica; Fernández García, Paula; González Fernández, Sonia (Psicooncología, 2014)
Objective: Based on a functional-contextual analysis of the problems cancer patients have, the efficacy of Behavioral Activation Therapy for the prevention of emotional disorders and the promotion of life quality on lung cancer patients will be analyzed. Method: A total of 90 lung cancer patients were selected consecutively. Patients were randomly assigned to un experimental group (G.E.: N=50) where a specific protocol was designed to increase relevant activities and healthy behaviors, erasing disease behaviors previously learned and modifying the pattern of experiential avoidance; and a control group (G.C.: N=40) where life quality and psychosocial effects of both illness and treatment were assessed, without ever offering counseling or psychological treatment. Both conditions received a total of four individual one hour long treatment sessions in the hospital. Results were collected through standardized scales (IK, HADS, QLQ-C30, EG y SP) in each of the treatment sessions and during the three months follow-ups. The evolution and tendency of the variables was analyzed using MLG y MLM. Results: Participants, doe to their clinical and sociodemographic characteristics resulted a representative group of the population studied and did not differ between themselves in the pre-treatment. In both groups there was a loss of subjects produced by hospitalization / death. The comparison analysis inter and intra groups indicate that among participants, the G. E. showed, over time, statistically significant differences (p< 0.05) in all subscales of QLQ- C30 functioning. In the HAD subscales, significant differences between groups in favor of GE (p<0.05) were achieved. Improvements shown by the G.E. weakened during the follow-up. Conclusions: Behavioral Activation Therapy, during cancer treatment, improved life quality and emotional adjustment. The study indicates the need to investigate the characteristics of patients and/or intervention, as its effectiveness and efficiency depends on them.